2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437635
|View full text |Cite
|
Sign up to set email alerts
|

Coded Caching with Heterogeneous Cache Sizes and Link Qualities: The Two-User Case

Abstract: Centralized coded caching problem is studied for the two-user scenario, considering heterogeneous cache capacities at the users and private channels from the server to the users, in addition to a shared channel. Optimal caching and delivery strategies that minimize the worst-case delivery latency are presented for an arbitrary number of files. The converse proof follows from the sufficiency of fileindex-symmetric caching and delivery codes, while the achievability is obtained through memory-sharing among a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…That is, the placement and delivery design must be such that the server does not participate in delivery at all, thus saving its resources to serve those outside the D2D network. This distinction calls for new placement and delivery schemes as compared to serve-based delivery architectures [10]- [15], [25]- [27]. In the same spirit as [13], we show that a linear program minimizes the D2D delivery load by optimizing over the partitioning of the files in the placement phase and the size and structure of the D2D transmissions, and find the optimal design.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…That is, the placement and delivery design must be such that the server does not participate in delivery at all, thus saving its resources to serve those outside the D2D network. This distinction calls for new placement and delivery schemes as compared to serve-based delivery architectures [10]- [15], [25]- [27]. In the same spirit as [13], we show that a linear program minimizes the D2D delivery load by optimizing over the partitioning of the files in the placement phase and the size and structure of the D2D transmissions, and find the optimal design.…”
Section: Introductionmentioning
confidence: 93%
“…More realistic caching models that reflect the heterogeneity in content delivery networks consider systems with distinct cache sizes [10]- [15], [25]- [27], unequal file sizes [26], [28], [29], distinct distortion requirements [25], [30], [31], and non-uniform popularity distributions [32]- [37]. In this work, we focus on the distinct cache sizes, i.e., the varying storage capabilities of the users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For systems with equal cache sizes, references [9], [10] have shown that coded placement is beneficial in the small memory regime when the number of files is less than or equal the number of users. Recent reference [11] has shown that coded placement is essential in achieving the optimal delivery load in a two-user system when the cache sizes of the two users differ.…”
Section: Introductionmentioning
confidence: 99%